2010
DOI: 10.1200/jco.2008.21.6606
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Authorship Contributions and Authors' Industry Financial Ties Among Oncology Clinical Trials

Abstract: A B S T R A C T PurposeTo test the hypothesis that authors who play key scientific roles in oncology clinical trials, and who therefore have increased influence over the design, analysis, interpretation or reporting of trials, are more likely than those who do not play such roles to have financial ties to industry. MethodsData were abstracted from all trials (n ϭ 235) of drugs or biologic agents published in the Journal of Clinical Oncology between January 1, 2006 and June 30, 2007. Article-level data included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Increasing author affiliations with industry were reported in several studies [64], [97], [99], as well as increased odds for authors reporting financial ties to industry [125]. The prevalence of ghost authorship was reported in the range from 2% to 75% [38], [50], [57], [92], [113].…”
Section: Resultsmentioning
confidence: 94%
“…Increasing author affiliations with industry were reported in several studies [64], [97], [99], as well as increased odds for authors reporting financial ties to industry [125]. The prevalence of ghost authorship was reported in the range from 2% to 75% [38], [50], [57], [92], [113].…”
Section: Resultsmentioning
confidence: 94%
“…This represents a significantly lower proportion compared with other disciplines, such as primary care, oncology, internal medicine/neurology, and psychiatry, in which 60%–80% reported funding. 5,2224 Our finding that supportive/palliative oncology research appears to be underfunded raises serious concerns because high-quality studies, such as randomized controlled trials, often require substantial investment of research dollars. This is supported by our observation that funding reporting is associated with prospective trials and larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…2628 Few published studies in supportive/palliative oncology reported industry ties, which is in stark contrast to other oncology articles, in which up to 52% reported pharmaceutical company support. 5,29 The relative lack of industry involvement may have contributed to the limited growth of pharmacological treatments in supportive/palliative oncology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with other studies outside of the palliative care literature [7,17,35], we also identified pharmaceutical industry funding to be associated with higher study quality. This finding is important since industry-sponsored studies have been shown to be associated with biased investigators [31], study design [19], analysis [23], and interpretation [1,5]. Thus, authors, editors, reviewers, and readers should not only place emphasis on the reporting of methodologic elements, but also the funding source and conflict of interest reporting.…”
Section: Discussionmentioning
confidence: 99%